Building Hinduism Educational Values-Based School Culture - I Made Girinata (Jurnal Penelitian Agama Hindu, 2020)
The purpose of this study was to describe the effort to build Hinduism Educational Values-based school culture. A school is a place of learning activities that are not only meant as an activity of transfer of knowledge from teacher to student but also an activity to familiarize the entire school community for discipline and compliance with regulations, mutual respect, clean and healthy life. The habits formed in the long journey of the school are called school culture, which in its development has not been able to form a character school community. Therefore, it is time for school culture to be built with not only limited to scientific values but all values of life including Hinduism Educational Values.